2015
DOI: 10.1051/0004-6361/201424845
|View full text |Cite
|
Sign up to set email alerts
|

Search for methylamine in high mass hot cores

Abstract: Aims. We aim to detect methylamine, CH 3 NH 2 , in a variety of hot cores and use it as a test for the importance of photon-induced chemistry in ice mantles and mobility of radicals. Specifically, CH 3 NH 2 cannot be formed from atom addition to CO whereas other NH 2 -containing molecules such as formamide, NH 2 CHO, can. Methods. Submillimeter spectra of several massive hot core regions were taken with the James Clerk Maxwell Telescope (JCMT). Abundances are determined with the rotational diagram method where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Previously, Di Francesco et al (2001) reported a similar kind of inverse P-Cygni profile and found that H 2 CO traces infall in IRAS 4A and they also detected the outflow from both 4A and 4B position by observing bright wing emission of H 2 CO. Formaldehyde, along with its deuterated counterpart, has also been observed in outflows toward other sources (e.g., Sahu et al 2018). The presence of H 2 CS in G31 has previously been reported by Ligterink et al (2015).…”
Section: Formaldehyde H2cosupporting
confidence: 54%
“…Previously, Di Francesco et al (2001) reported a similar kind of inverse P-Cygni profile and found that H 2 CO traces infall in IRAS 4A and they also detected the outflow from both 4A and 4B position by observing bright wing emission of H 2 CO. Formaldehyde, along with its deuterated counterpart, has also been observed in outflows toward other sources (e.g., Sahu et al 2018). The presence of H 2 CS in G31 has previously been reported by Ligterink et al (2015).…”
Section: Formaldehyde H2cosupporting
confidence: 54%
“…A tentative detection was done in Orion Kl by Pagani et al 194 . Non-detections led to upper limit in a number of highmass young stellar objects (YSOs) 195 or in the low-mass Sun-like protostar IRAS 16293-2422B where the abundance of methylamine was determined to be two orders of magnitude lower than in Sgr B2 196 .…”
Section: An Important Prebiotic Speciesmentioning
confidence: 99%
“…There are significant non-detections in some regions: for example, species such as methylamine, CH3NH2, and hydroxylamine, NH2OH, have been sought due to their potential roles as precursors for amino acids. However, so far only CH3NH2 has been detected in the ISM and only toward a few select regions such as Sgr B2(N) (Kaifu et al 1974), Orion KL (Pagani et al 2017), G10.47+0.03 (Ohishi et al 2019), and NGC 6334 (Bøgelund et al 2019b), but not in general toward high-mass star forming regions or low-mass protostars (Ligterink, Tenenbaum & van Dishoeck 2015;Ligterink et al 2018a). No secure detection of NH2OH has been reported so far despite dedicated searches toward high- (Pulliam, McGuire & Remijan 2012) and low-mass star forming regions (McGuire et al 2015;Ligterink et al 2018a).…”
Section: Detections In the Warm Gas Of Hot Cores And Corinosmentioning
confidence: 99%